Vidéo-élicitation et parole empêchée dans le nucléaire - Pascal Cesaro; Pierre Fournier; Joyce Sebag; Jean-Pierre Durand (La Nouvelle Revue du Travail)
Based on the twofold observation that sociologists run the risk of imposing issues and themes on their interviewees that are sometimes foreign to them, and that interviewees’ ability to speak about work is more or less impeded in a number of circumstances, Pascal Cesaro (filmmaker) and Pierre Fournier (sociologist) propose to conduct surveys using video-elicitation. The interview they give here shows the heuristic potential of the approach, while also exposing the difficulties of the undertaking and its pitfalls. They go into detail about their practice and the reasons for the choices it entailed, such as selecting the sequences to be debated or favoring fiction as the genre of images to be presented to the interviewees. The result is a sociological documentary, both rigorous and stimulating to watch, from which they have subsequently produced an interactive documentary, visible on the web, to explain their approach.